Geological controls on the geothermal system and hydrogeochemistry of the deep low-salinity Upper Cretaceous aquifers in the Zharkent (eastern Ily) Basin, south-eastern Kazakhstan - Kozhagulova, Ashirgul; Yapiyev, Vadim; Karabayanova, Leila; Dillinger, Antoine; Zavaley, Vyacheslav; Kalitova, Aisulu; Bayramov, Emil; Holbrook, John; Grasby, Stephen E.; Fustic, Milovan (Frontiers in Earth Science, 2023)
The Zharkent (eastern Ily) Basin is renowned for its low-salinity natural hot springs and geothermal wells, primarily utilized for recreational purposes. Despite the growing commercial interest, the geothermal system in this area is very poorly documented or understood. Accordingly, we conducted a multi-disciplinary study, focusing on the advanced characterization of waters from productive Cretaceous strata, along with the interpretation of geothermal gradients and reservoir recharge in a geological context. Conventional wisdom asserts that Ily is an intracratonic basin characterized by high geothermal heat in its central part and by geothermal aquifers that are rapidly replenished by meteoric water recharge via porous strata exposed on the basin margin. Our results argue for an alternative and expanded interpretation of these systems. Elevated geothermal gradients (with average of up to 40 °C/km in the southern part of the basin and locally possibly up to 55 °C/km) are likely associated with crustal thinning owing to the development of a pull-apart basin. Anomalously fresh water (< 1 g/L) in the deep (up to 2850 m depth) Upper Cretaceous reservoir is charged laterally, predominantly by snowmelt waters from basin bounding mountains. Recharge includes both mountain-front recharge (MFR), where water infiltrates into outcrops of reservoir rock near the mountain fronts, and mountain-block recharge (MBR), characterized by deep groundwater flow through fractured, predominantly rhyolite basement rocks (as evidenced from their solutes in reservoir waters). The combination of elevated geothermal gradients, low salinity water chemistry, and excellent reservoir properties makes the studied reservoir horizon an attractive target for geothermal development. Our results are applicable to other geothermal systems in strike-slip settings across Central Asia, and potentially worldwide.